Structural Change, Wage Formation and Economic Growth in Low-Income Countries - Dieter Bender (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2012)
This paper analyzes the effects of structural change on the rates of growth of wages, employment and per-capita income in low-income countries, their dualistic structure shown by a Lewis-type two-sector model. Structural change is measured by the varying shares of sectoral employment in total employment. It is shown that the growth rates of GDP and per-capita income can be formulated as functions of these sectoral employment shares. Distinguishing the phases of dualistic development with and without labour surplus and post-dualistic development, it is demonstrated that each of these stages exhibits different growth dynamics: high but falling growth rates under dualistic development with labour surplus, low but rising growth rates under dualistic development after absorption of the labour surplus, growth rates falling again and converging toward a higher income steady state in the post-dual economy. As the growth dynamics of dualistic development are explained by a modified Lewis model and those of post-dualistic development by the Solow model, the study also highlights the complementary roles both models are playing in development economics.
Keywords: O11; O41; 330; Economic growth; Dualistic development; Labour surplus; Rural-urban migration; Dualwirtschaft; Strukturwandel; Lohnbildung; Wirtschaftswachstum; Entwicklungstheorie; Landflucht; Theorie